Purification and characterization of a flavor-related enzyme, γ-glutamyl-transpeptidase, from Toona sinensis leaves. Issue 6 (1st November 2016) - Liu, Chang-Jin; Jia, Jian-Ying; Wang, Hao-Yu; Xue, Li-Li; Kong, Yu; Wang, Fu-Xin
ABSTRACT: A flavor-related enzyme from Toona sinensis (TS), ɣ-glutamyl-transpeptidase (GGT), was purified 40.67-fold with 13.40% recovery using ammonium sulfate precipitation, dialysis and gel filtration chromatography. Gel filtration chromatography and sodium dodecyl sulfate acryl amide gel electrophoresis (SDS-PAGE) revealed that GGT was a heterodimer with a molecular weight of 90 kDa, and the molecular size of its two subunits was 26 kDa and 64 kDa, respectively. The apparent Km and Vmax of GGT were 3.623 μmol/mL and 2.831 μmol/mL/min of protein, respectively. The optimum reaction temperature was 60°C, while the optimum pH was 7.0. GGT can tolerate temperatures of 70°C for a short time and can keep stable activity at 60°C for more than 2 hours. The effect of metal ions on GGT activity showed that Cu 2+ and Zn 2+ had strong inhibition, while Fe 3+ had strong activation, and other metal ions had only a slight effect. LC-MS analysis indicated that GGT catalyzed (S, S)-γ-glutamyl-(cis-S-1-propenyl)-thioglycine, a flavor precursor found in TS, to release glutamic acid moiety.